THE ROLE AND SIGNIFICANCE OF VOICES IN TRADITIONAL SINGING PERFORMANCE (Web of Teachers: Inderscience Research, 2026)
This article provides information about the various forms of traditional Uzbek music, which are distinguished by the highest examples of national performance style and vocal interpretation, the main criteria for pure timbre, expressive and perfect interpretation, wide range, unique volume and skill of the voice. In particular, the article discusses the Fergana-Tashkent traditions of Uzbek national vocal art, first of all, the qualitative characteristics of the voice of performers and methods of its use, the terms of their main types, divided into several categories.